Molecular detection of blaOXA-23, csuE and ompA genes from carbapenem-resistant and biofilm producing Acinetobacter baumannii isolated from clinical samples - Thapa, Jeena; Sah, Anil Kumar; Paudel, Pratik; Chandra, Avinash; Upreti, Milan Kumar (Journal of Nepal Biotechnology Association, 2025)
Acinetobacter baumannii has become a critical hospital pathogen due to its biofilm formation and multidrug resistance, particularly against carbapenems. This study aimed to detect blaOXA-23, ompA and csuE genes in carbapenem-resistant, biofilm-producing A. baumannii in clinical isolates. Among 521 clinical samples, 39 MDR and carbapenem-resistant isolates were selected. Antibiotic susceptibility was tested via Kirby-Bauer disc diffusion with carbapenemase production confirmed by the combined-modified carbapenem inactivation method. Biofilm production was assessed by congo red agar and modified microtiter plate assay. PCR was used to detect blaOXA-23, ompA and csuE genes. All isolates were resistant to ceftazidime and ampicillin but sensitive to colistin. Of the 39 isolates, 29 produced biofilms (10 strong, 7 moderate, 12 weak and 10 non-biofilm producers). The prevalence of blaOXA-23, ompA and csuE genes was 61.53%, 41.02%, and 46.15%, respectively with a significant correlation between antibiotic resistance, biofilm formation and gene presence. The high prevalence of MDR A. baumannii with biofilm-associated genes and carbapenem resistance in hospitals highlights the need for stringent control measures and regular monitoring.